Evaluation Independence in Organizations - Robert Picciotto (The Evaluation Center at Western Michigan University, 2013)
Background: Evaluation independence is a neglected issue in the literature. Yet, it is a critical aspect of evaluation governance in organizations.   Purpose: The article draws on organizational theory, institutional economics and international development evaluation practice to define evaluation independence in organizations, outline principles geared to the design of evaluation processes within organizations and trigger a debate on evaluation independence in the evaluation community.   Intervention: Not applicable.   Research Design: Literature review informed by personal exposure to management of the World Bank Independent Evaluation Group.   Data Collection and Analysis: Not applicable.   Findings: Independent and self-evaluation are complementary and synergistic. Organizational theory demonstrates that a judicious combination of independent and self-evaluation contributes to managerial accountability and double loop learning.   Keywords: independence; accountability; internal evaluation; external evaluation; double loop learning